2019
DOI: 10.2174/1573399815666190425182008
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Clinical Effectiveness and Tolerability of Hydroxychloroquine 400 Mg in Uncontrolled Type 2 Diabetes Subjects who are not Willing to Initiate Insulin Therapy (HYQ-Real-World Study)

Abstract: Objective: The epidemic of T2DM is rising across the globe. Systemic inflammation plays a pivotal role in the pathogenesis and complications of T2DM. Combination of two or more oral hypoglycemic agents (OHA) is widely prescribed in patients with T2DM, however many patients have poor glycemic control despite receiving combination therapy. The new antidiabetic drugs are relatively costly or many patients have anxiety over the use of injectable insulin. The objective of this observational study was to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…24 Among 250 patients with poorly controlled type 2 diabetes who were unwilling to start insulin, hydroxychloroquine (400 mg/d) was associated with marked reductions in fasting plasma glucose, hemoglobin A 1c and body weight, whereas hypoglycemia developed in 2% of participants over the 48-month study period. 25 Physicians should warn patients who are being treated with chloroquine or hydroxychloroquine about the possibility of hypoglycemia and describe its manifestations. Management of hypoglycemia involves cessation of the drug and administration of supplemental glucose or parenteral dextrose as needed.…”
Section: Hypoglycemiamentioning
confidence: 99%
“…24 Among 250 patients with poorly controlled type 2 diabetes who were unwilling to start insulin, hydroxychloroquine (400 mg/d) was associated with marked reductions in fasting plasma glucose, hemoglobin A 1c and body weight, whereas hypoglycemia developed in 2% of participants over the 48-month study period. 25 Physicians should warn patients who are being treated with chloroquine or hydroxychloroquine about the possibility of hypoglycemia and describe its manifestations. Management of hypoglycemia involves cessation of the drug and administration of supplemental glucose or parenteral dextrose as needed.…”
Section: Hypoglycemiamentioning
confidence: 99%
“…Furthermore, patients with higher baseline hs-CRP levels also exhibited higher (although not significant) baseline levels of HbA1c, fasting-and postprandial glucose levels. (5) The previously mentioned study by Wasko et al (4) conducted in non-diabetic overweight or obese subjects also found that HCQ (at a dose of 400 mg/day) significantly increased plasma levels of the adipokine adiponectin, which plays a key role in insulin resistance and metabolic syndrome by exerting anti-inflammatory actions and increasing insulin sensitivity. (31)(32)(33) Importantly, HCQ use up to 24 weeks (at a dose of up to 600 mg/day) in patients with T2D has also led to an improved lipid profile, which consisted of a significant reduction in total cholesterol, LDL-cholesterol and non-HDL cholesterol in different studies.…”
Section: Antihyperglycemic Properties Of Hcq: Current Mechanistic Evimentioning
confidence: 87%
“…Different studies have shown the safety and efficacy of HCQ use (at a dose ranging from 400 to 600 mg/day) in patients with T2D over a short-term period (up to 18 months). (5,11,12,14,15) In 2014, HCQ (at a dose of 400 mg/day) has been approved in India as an addon hypoglycemic agent for patients with inadequately controlled type 2 diabetes despite lifestyle management associated with sulfonylurea and metformin combination therapy. Nevertheless, concerns on long-term safety of HCQ in patients with T2D still persist due to the lack of robust data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations